Work and Risks of Illness:: A Study among Policemen - Anchieta, Vânia Cristine (2011)
The purpose of this study was to evaluate the perception of police officers in Brasilia regarding the context in which they work. Their demands and experiences, as well as physical, psychological and social disorders caused by their professional activities were analyzed. Inferences were made about mediation strategies used to prevent suffering and the risks of illnesses. The Inventory of Work and Illness Risks was answered by 160 police officers, both men and women, who recently joined the institution (average of eight months on the force). Results indicated that although serious damage to the health of new police officers was not evident, there are risks of flaws in mediation strategies regarding factors which lead to disorders.